Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar: (Studi Observasi di Sd Binekas Bandung) (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Learning evaluation is a crucial element in education because it serves to assess the achievement of learning objectives. Advances in digital technology encourage educators to utilize digital tools in implementing learning evaluations, particularly at the elementary school level. This study aims to describe the implementation of digital-based learning evaluations at Binekas Elementary School, Bandung, and identify the advantages and challenges faced in its implementation. The approach used in this study is descriptive qualitative, using observation and documentation methods. The research findings indicate that digital-based learning evaluations have been conducted using media such as Google Forms, Quizizz, and Wordwall. The use of these digital media offers advantages in terms of time efficiency, ease of processing evaluation results, and increased student motivation and participation. However, the implementation of digital-based evaluations still faces obstacles such as a lack of facilities, limited internet access, and teacher preparedness. Therefore, support for facilities and improvement of teacher skills are needed to ensure optimal implementation of digital-based learning evaluations in elementary schools.